The role of servant leadership in reducing job bullying: Analytical research in the General Company for Electrical and Electronic Industries (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The current research aims to identify the impact of servant leadership in reducing workplace bullying behaviors, given the importance of these variables in industrial organizations and their impact on their survival and growth in light of rapid technological developments. The field research problem was represented by the weakness of awareness of the importance of servant leadership and its dimensions (empowerment, humility, vision, trust, moral love) and neglecting its role in reducing workplace bullying in its dimensions (abuse of the individual (personality), abuse during work, contempt), so the research came to direct the attention of the General Company for Electrical and Electronic Industries to the need to pay attention to the research variables. To achieve this goal, the analytical (descriptive) approach was relied upon. The researcher used the questionnaire as the main tool for collecting data. The questionnaire was distributed to a sample of male and female department heads. A number of statistical techniques were used within the program (SPSS V.24, Microsoft Excel 2010) such as (weighted arithmetic mean, standard deviation, relative coefficient of variation, relative importance, simple linear regression and path analysis to process the collected data to reach the results to achieve the research objectives. The most important results reached by the current research are the presence of a direct positive effect between the variables studied, as the results showed that severe and repeated orders from management led to increased levels of stress among employees, which negatively affected their psychological and physical health. In addition, severe pressure leads to a decrease in productivity due to continuous stress and fatigue, which affects the quality and efficiency of work. The constant feeling of pressure prompts employees to look for other job opportunities, which increases the rate of employee turnover and affects the stability of the company.